2009
DOI: 10.1007/s12350-008-9019-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of fusion of myocardial perfusion imaging (MPI) and computed tomography coronary angiography

Abstract: Background We evaluated the incremental diagnostic value of fusion images of coronary computed tomography angiography (CTA) and myocardial perfusion imaging (MPI) over MPI alone or MPI and CTA side-by-side to identify obstructive coronary artery disease (CAD > 50% stenosis) using invasive coronary angiography (ICA) as the gold standard. Methods 50 subjects (36 men; 56 ± 11 years old) underwent rest-stress MPI and CTA within 12-26 days of each other. CTAs were performed with multi-detector CT-scanners (31 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(61 citation statements)
references
References 10 publications
1
56
0
4
Order By: Relevance
“…Fourth, although care was taken to match individual coronary anatomy to perfusion territories in the evaluation of the PET/CTCA scan, software to generate fusion images of CTCA and PET was not commercially available from the manufacturer of our installed system. Some studies have demonstrated that fused hybrid imaging as compared with side-by-side analysis may slightly improve diagnostic accuracy (34)(35)(36). Finally, parametric perfusion images were generated by different software packages developed in-house in both studies (12,37).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although care was taken to match individual coronary anatomy to perfusion territories in the evaluation of the PET/CTCA scan, software to generate fusion images of CTCA and PET was not commercially available from the manufacturer of our installed system. Some studies have demonstrated that fused hybrid imaging as compared with side-by-side analysis may slightly improve diagnostic accuracy (34)(35)(36). Finally, parametric perfusion images were generated by different software packages developed in-house in both studies (12,37).…”
Section: Discussionmentioning
confidence: 99%
“…SPECT-MPI and FFR are established standards for determining the functional significance of coronary stenosis inducing perfusion defects, which is valuable for guiding therapeutic plans and helping with prognostic assessments of patients [24][25][26][27][28][29]. CMR-MPI is an alternative to SPECT for detecting anatomically significant stenoses with better sensitivity and NPV compared with ICA [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 50 patients, it was demonstrated that combining MPI and CT coronary angiography increased the overall area under the curve for the presence of CAD in any vessel; however, there was no trend for increased sensitivity for multivessel CAD. 34 Although this could be seen as an improvement in the diagnostic power of a patient visit, these ''one-stop-shop'' approaches have not been embraced by the payer community and can add significantly to the patient's radiation dose.…”
Section: Hybrid Image: For Attenuation Correction Only or Additional mentioning
confidence: 99%